PENGARUH VARIASI SUDUT BUKAAN GUIDE VANE TERHADAP KINERJA PROTOTYPE PLTMH DENGAN TURBIN KAPLAN - Sudiatmika, I Nyoman; Arta Wijaya, I Wayan; Suartika, I Made (Jurnal SPEKTRUM, 2021)
The increase in the need for electrical energy in Indonesia is increasing along with population growth. Followed by the depletion of fuels originating from fossil energy. Based on geographic conditions, Indonesia has many rivers so that it has the potential to generate electricity by utilizing the flow of water which is called PLTMH (Microhydro Power Plant). In realizing this PLTMH, one type of water turbine can be used, namely the Kaplan turbine, where this type of turbine works at low head conditions with large discharge. The purpose of this research is to analyze the performance of the Kaplan type turbine guide vane prototype at angles of 15º, 30º, 45º, 60º, 75º, and 90º to meet the electricity demand in Indonesia. After being examined based on all the variations tested, the maximum value of the turbine rotational speed at an opening of 15º with the rotation values obtained before and after coupled with the generator were 249.5 rpm and 216.5 rpm. The value of the generator rotation before and after the 30 Watt load coupling is 1096.6 rpm and 999 rpm. Voltage, current, and power produced are 9,1 Volts, 0,68 Amperes, and 6,18 Watts. The resulting torque of 0,27 Nm. The greatest efficiency was obtained at a combination of the opening angle of the guide vane of 15º at 2,62%.